Control of COVID‐19 Outbreaks under Stochastic Community Dynamics, Bimodality, or Limited Vaccination. Issue 23 (23rd May 2022) - Goldenbogen, Björn; Adler, Stephan O.; Bodeit, Oliver; Wodke, Judith A. H.; Escalera‐Fanjul, Ximena; Korman, Aviv; Krantz, Maria; Bonn, Lasse; Morán‐Torres, Rafael; Haffner, Johanna E. L.; Karnetzki, Maxim; Maintz, Ivo; et al.
Abstract: Reaching population immunity against COVID‐19 is proving difficult even in countries with high vaccination levels. Thus, it is critical to identify limits of control and effective measures against future outbreaks. The effects of nonpharmaceutical interventions (NPIs) and vaccination strategies are analyzed with a detailed community‐specific agent‐based model (ABM). The authors demonstrate that the threshold for population immunity is not a unique number, but depends on the vaccination strategy. Prioritizing highly interactive people diminishes the risk for an infection wave, while prioritizing the elderly minimizes fatalities when vaccinations are low. Control over COVID‐19 outbreaks requires adaptive combination of NPIs and targeted vaccination, exemplified for Germany for January–September 2021. Bimodality emerges from the heterogeneity and stochasticity of community‐specific human–human interactions and infection networks, which can render the effects of limited NPIs uncertain. The authors' simulation platform can process and analyze dynamic COVID‐19 epidemiological situations in diverse communities worldwide to predict pathways to population immunity even with limited vaccination. Abstract : The limits of control and the effect of measures against future COVID‐19 outbreaks are identified using a detailed community‐specific ABM. The demographic and geographic structure of assessed communities influence the pattern of infection spreading and the resulting R ‐values. Stochastic community dynamics and limited vaccination can lead to bimodal outcomes, rendering predictions about infection spreading and effects of nonpharmaceutical interventions uncertain.